Leituras infantis da televisão: uma análise do Programa TV Globinho - Silva, Patrícia Soares da (2005)
The objective of this study is to investigate the “reworking” of television messages, based on daily observations of two groups of students. How does the infant public understand and take in these messages? How are these messages incorporated into children’s daily life? Such questions are crucial to understanding the program/child relationship. Therefore, I selected ten children from different social positions, five from the “lower class”, and five from the “middle class”. The ethnographic description was one of the methodological procedures adopted in the study. To this end, I used the techniques of participatory observation and interview. The program “TV Globinho” (shown on Globo Network) was chosen for analysis. The observations were made while the children watched the aforementioned program, as well as during other coordinated practice activities (Games, domestic chores, conversations with friends, etc…).In addition to the anecdotes collected from the children, I also interviewed the parents of the children involved in the study. These interviews offered me the chance to observe the child audience within the context of their home environments. This was useful because the family is an important mediator in the meaning of television messages, especially for children.